(untitled) (Medical Forum Monthly, 2022)
Objective: To evaluate and compare knowledge, attitude, and behaviors among medical postgraduates (MPG) and dental postgraduates (DPG) regarding Photodynamic therapy (PDT). Study Design: Cross sectional Survey study Place and Duration of Study: This study was conducted at the Department of Restorative and Prosthetic Dentistry, College of Dentistry, Dar Al Uloom University, Riyadh, Saudi Arabia from January 2021 to March 2021. Materials and Methods: A questionnaire registered on www.surveys.google was used. The sample size was 433 participants. Total 387 health professionals responded with 89 % of response rate. Contact details of registered DPG and MPG were requested from the office of Saudi Commission for health Specialist. The questionnaire comprised of four sections. The first section is comprised of socio-demographics. The second domain inquired about knowledge i.e., invasiveness, mechanism of action, and photosensitizers. The third section investigated attitude in clinical practice. Whereas the fourth section of the questionnaire inquired about behavior and willingness to offer PDT as a treatment option. Statistical Package for the Social Sciences was used to analyse data. Descriptive analysis was performed and the result was presented in the form of mean, frequencies, and percentages. Results: Most MPG displayed adequate knowledge, 80%, 82%, and 79% were aware of the invasiveness, mechanism of action, and role of photosensitizers in PDT respectively. Whereas, DPG displayed inadequate knowledge. Similarly, MPG demonstrated a better attitude towards PDT. A notable result signifies an extraordinary response of MPG for discussing PDT as a treatment alternative with their patients. When inquired about the recommendation of therapeutic benefits of PDT, 65% of MPG and 40% of DPG recommends PDT in their practice. Role to treat cancer and acne was well-known among MPG (90%) whereas dental trainees did not exhibit adequate behavior Conclusion: DPG showed inadequate knowledge regarding PDT. However, their response presented keenness in acquiring knowledge through training and workshops. On the contrary, MPG exhibited satisfactory knowledge and behavior towards PDT.